Escolas do campo e atendimento educacional especializado em sala de recursos multifuncional - Palma, Debora Teresa [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Special education in the inclusive perspective has been discussed in several researches. However, there are few articles that treat disabled people who live and study in the country. Because of this, the aim of this research was to analyze the Specialized Education Attendance (SEA) developed in the country schools. The research followed a qualitative approach and had as a methodological procedure the Case Study. For data obtaining, questionnaires were used as well as observation, photographic register and analysis of school documents. The research was performed in three country schools located in an inner city of São Paulo state with thirty-one teachers of regular teaching. From these, seventeen were responsible by the students met by the SEA service, and the researcher, given that the Special Education Teacher is active in the Multifunctional Resources Classroom of the selected schools.The results of the observation revealed that only one school has adequate space for the functioning of the Multifunctional Resources Classroom. The kind of deficiency found in all three schools is the intelectual, and the organization of one Special Education teacher to attend the three units is not enough. In addition, it was identified that these students take part of the SEA in the same school shift due to the transportation difficulty, diverging of the proposal established in legislation. The data analyzed from the teachers' questionnaire point out the attitudinal change of the teachers in considering the disabled students as public of regular teaching and they also reinforce the little contact for orientation with the expert teacher. Finally, the results of the familiar questionnaire point out that the family does not see their children's difficulties as a deficiency. It is hoped that this study can subsidize the debate for the construction of public politics that consider the particularities of the disabled people who live and study in the country.

A Educação Especial na perspectiva inclusiva está sendo discutida em diversas pesquisas, no entanto, são poucos os trabalhos que tratam das pessoas com deficiência que vivem e estudam em escolas do campo. Tendo isso em conta, esta pesquisa teve como objetivo analisar o Atendimento Educacional Especializado (AEE) desenvolvido em escolas do campo. A pesquisa seguiu uma abordagem qualitativa e teve como procedimento metodológico o Estudo de Caso, para construção dos dados utilizaram-se questionários, observação, registro fotográfico e análise dos documentos escolares. Foi realizada em três escolas do campo localizadas em um município do interior de São Paulo e os participantes foram 31 professores de ensino regular, 17 responsáveis pelos alunos atendidos pelo serviço de AEE e a pesquisadora, tendo em vista que esta é a Professora de Educação Especial atuante na Sala de Recursos Multifuncional das escolas selecionadas. Os resultados das observações revelaram que apenas uma escola possui espaço adequado para funcionamento da Sala de Recursos Multifuncional, o tipo de deficiência encontrado nas três escolas é a intelectual e a organização de uma Professora de Educação Especial para atender as três unidades é insuficiente, além disso, foi identificado que estes alunos participam do AEE no mesmo turno escolar devido às dificuldades do transporte, divergindo da proposta estabelecida na legislação. Os dados analisados a partir dos questionários dos professores apontam a mudança atitudinal dos mesmos em considerar o aluno com deficiência como público do ensino regular e também reforçam o pouco contato para orientação com a Professora Especialista. Por último, os resultados do questionário dos familiares apontam que eles não percebem a dificuldade dos filhos como deficiência. Espera-se que este estudo possa subsidiar o debate para construção de políticas públicas que considerem as particularidades das pessoas com deficiência que vivem e estudam no campo.
Country schools and specialized education attendance in multifunctional resources classroom
Keywords: Country education; Specialized education attendance; Educational inclusion; Educação do campo; Atendimento educacional especializado; Educação inclusiva